2009
DOI: 10.1103/physrevlett.103.045005
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Kelvin-Helmholtz Instability in a High-Energy-Density Plasma on the Omega Laser

Abstract: A laser initiated experiment is described in which an unstable plasma shear layer is produced by driving a blast wave along a plastic surface with sinusoidal perturbations. In response to the vorticity deposited and the shear flow established by the blast wave, the interface rolls up into large vortices characteristic of the Kelvin-Helmholtz instability. The experiment used x-ray radiography to capture the first well-resolved images of Kelvin-Helmholtz vortices in a high-energy-density plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…Wave crests begin to develop immediately after passage of the shock wave and grow into fully developed vortices (middle frame). At late time (right frame), the spiral arms of the vortices appear to begin to diffuse away presumably the result of the onset of turbulence (figure adapted from Hurricane et al 2009;Harding et al 2009) compared with simulation and theory. In Fig.…”
Section: Instability Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Wave crests begin to develop immediately after passage of the shock wave and grow into fully developed vortices (middle frame). At late time (right frame), the spiral arms of the vortices appear to begin to diffuse away presumably the result of the onset of turbulence (figure adapted from Hurricane et al 2009;Harding et al 2009) compared with simulation and theory. In Fig.…”
Section: Instability Growthmentioning
confidence: 99%
“…In May 2008, our team fielded the first successful highenergy-density-plasma (HEDP) Kelvin-Helmholtz (KH) experiments Harding et al 2009) on the Omega laser at the University of Rochester. These experiments demonstrated the conceptual design (Hurricane 2008) that relied upon shock driven baroclinic vorticity production and also showed that vivid high quality data (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] However, the development of high-energy laser facilities has enabled dynamic fragmentation experiments that employ intense laser irradiation, where, in most cases, particle size data of the ejecta have been obtained by means of a new technique involving postshock analysis of targets and recovered fragments. 3,5,[17][18][19] However, to date, the x-ray backlighting technique, which has been widely used to analyze and image plasmas in hydrodynamic experiments, [20][21][22][23][24][25][26] has not been used to study this phenomenon. With the advantages that the motion blur can be neglected owing to the short pulse of the driven laser beams, x-ray backlighting can clearly image high-velocity objects, and these images can be used to derive reliable mass density distribution of the objects.…”
Section: Introductionmentioning
confidence: 99%
“…Further, virtually any HED shock-driven hydrodynam-ics experiment will involve this kind of preheat effect, because they generally require one to irradiate a particular surface, and then wait some amount of time for a shock to form and propagate to another location [9,[29][30][31][32][33][34][35]. These systems often involve a material interface with seeded interface structure, and it is often assumed or approximated that the prefabricated initial conditions and the conditions encountered by the shock are identical.…”
Section: Introductionmentioning
confidence: 99%